Saintific Approach in 21st Century Learning in Indonesian Language Learning Vocational School of Pharmacy - Chuntala, Angela Diyansih Wisesa (International Journal of Active Learning, 2019)
The current learning process has reached the 21st century where information is widely spread and technology is developing. The characteristics of the 21st century are marked by the interrelation of the world of science so that it synergizes faster (BNSP, 2010). The 21st century is also marked by the number of (1) information that is available anywhere and can be accessed at any time; (2) faster computing; (3) automation that replaces routine jobs; (4) communication that can be done from anywhere and anywhere (Litbang Kemendikbud, 2013). The things above are also in line with learning in Vocational High Schools (SMK). Muhadjir Effendy (Mendikbud) conveyed that the Vocational curriculum is in accordance with the needs of the business and industrial world (DUDI) and the Indonesian National Work Competency Standards (SKKNI). These things are also applied in learning Indonesian. Learning Indonesian based on a scientific approach aims to increase intellectual ability to think high-level students (Lutfiyah, 2015: 3). Indonesian subjects in the 2013 curriculum use a text-based approach (Lutfiyah, 2015: 4).